Exploring the Influences on Leadership Skills Development Among Dance Students at a Normal University in Lanzhou, China - Ting, Yin (Scholar: Human Sciences, 2025)
Purpose: This study explores the factors impacting dancing students' leadership competencies in a normal university in Lanzhou, China. The variables used in this research framework include core personality, emotional intelligence competencies, involvement, attitude, behavior, and environment on students' leadership competencies. Research Design, Data, and Methodology: The study aims to assess the current levels of these variables, design and implement Intervention Design Implementations (strategic plans) to enhance them, and determine their changes pre- and post-strategic plan. The research design was a sequential exploratory mixed-methods design, combining qualitative and quantitative methods to develop an instrument for data collection. The target population was dance students at Lanzhou, the first normal university in China, with a sample size of 494 students. Results: Preliminary findings revealed that the core personality, emotional intelligence competencies, involvement, attitude, behavior, and environment levels were generally low. A multiple regression analysis showed that core personality (β=0.136, p=0.001<0.05), emotional intelligence competencies (β=0.186, p=0.000<0.05), involvement (β=0.163, p=0.004<0.05), attitude (β=0.123, p=0.009<0.01), behavior (β=0.179, p=0.000<0.05), and environment (β=0.138, p=0.001<0.05) significantly predicted students' leadership competencies. Conclusions: Based on the findings, a theoretical model was developed and validated by experts, providing strategic planning and a foundation for future interventions to enhance students' leadership competencies.